Peculiarities of pedagogical staff professional training for work at ukrainian pre-school educational institutions in US and Canadian diaspora (2nd half of the xx century) - Rudnytska-Yuriichuk, Iryna (Iasi : UK : Lumen Publishing House, 2020)
The article discusses the peculiarities of organization and work of Ukrainian preschools in the Ukrainian diaspora in Canada and U.S., which aim to develop children’s national identity. Realization of the fact that in countries of settlement, namely in the USA and Canada, a considerable number of the new generation are losing their identity and getting disattached from the Ukrainian community has encouraged progressive community to create grounds for common solving of the problems of pre-school education both on the first and the main stages of external assistance provided to families in bringing up the nationally conscious new generation of the Ukrainians living overseas. We believe it is necessary to point out that organizers of Ukrainian preschool education in Canada and the USA, as well as in other countries of Ukrainian settlement, were well aware of the fact that in addition to study and material base and methodological provision, it is also necessary to have professionally trained kindergarten teachers for starting a children’s nursery school or a kindergarten. There were not enough of them, though. That was why a need for a pre-school education teacher arose.
Keywords: national mentality; nursery schools; pedagogue (teacher); sadochok (pre-school classes); Ukrainian diaspora; Ukrainian kindergarten